A Factual Assessment of the Draft Common Frame of Reference. - Group, Common Core Evaluating (Sellier. european law Publishers, 2010)
HauptbeschreibungThis book contains a case-based assessment of the Draft Common Frame of Reference carried out by the Common Core Evaluating Group, which gathers a number of well-established and younger scholars coming from Eastern and Western countries of the European Union using the working method of the research project "The Common Core of European Private Law" (www.common-core.org). The aim of the assessment is to test how the Draft Common Frame of Reference could work when applied in different national legal systems. To this end, a number of factual situations, i.e. hypothetical cases, ha.